2020
DOI: 10.1088/1757-899x/867/1/012031
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of specific chloroacetanilides on granular activated carbon

Abstract: Pesticides, as one of the main monitored micropollutants these days, are monitored and determined even in the drinking water, because of their toxic effect on the living organisms. Presence of these pesticides in the drinking water is undesirable and, therefore, they need to be removed. Chloroacetanilides belong to the group of herbicides, which are commonly used in agriculture. Their complex structure prevents common biological degradation, so more complex processes are needed. One of the most efficient proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Ormad et al 85 observed 75% removal of alachlor and metolachlor in a 5-min contact time with a 10 mg L −1 PAC dose. Conversely, Marton et al 33 achieved 48% removal of alachlor using 200 mg Filtrasorb 400 GAC after 60 min of contact.…”
Section: Adsorption Isotherm Modelsmentioning
confidence: 98%
See 1 more Smart Citation
“…Ormad et al 85 observed 75% removal of alachlor and metolachlor in a 5-min contact time with a 10 mg L −1 PAC dose. Conversely, Marton et al 33 achieved 48% removal of alachlor using 200 mg Filtrasorb 400 GAC after 60 min of contact.…”
Section: Adsorption Isotherm Modelsmentioning
confidence: 98%
“…30 Several adsorption studies on the removal of alachlor, acetochlor, metolachlor and fenthion from water and wastewater were reported in the literature. [32][33][34][35][36][37] However, the presence of natural organic matter (NOM) in water resources may pose complications in the effective removal of pesticides, especially because lowmolecular-weight organics have compelling competitive effects in removing micropollutants through the adsorption process. [38][39][40] The studies on pesticide removal by HNO 3 -and ClSO 3 H-modified AC in the literature are limited.…”
Section: Introductionmentioning
confidence: 99%
“…GAC 1240W activated carbon (GAC), purchased from Norit (Utrecht, The Netherlands), was selected as the adsorbent for the experiment. The reason for this is that this adsorbent is widely used in water treatment plants [8,18,19]. Its textural properties were studied using low-temperature nitrogen adsorption/desorption isotherms.…”
Section: Chemicalsmentioning
confidence: 99%
“…Based on the results of these tests, the basic structure parameters were estimated-specific surface area SBET = 900 m 2 g −1 , external surface area SEXT = 523 m 2 g −1 , total pore volume Vt = 0.52 cm GAC 1240W activated carbon (GAC), purchased from Norit (Utrecht, The Netherlands), was selected as the adsorbent for the experiment. The reason for this is that this adsorbent is widely used in water treatment plants [8,18,19]. Its textural properties were studied using low-temperature nitrogen adsorption/desorption isotherms.…”
Section: Chemicalsmentioning
confidence: 99%
“…The advantages and disadvantages of each of the different techniques are presented in Table 1 15 19 . However, the most efficient and the most widely used way to arrest pesticides contained in water streams is adsorption on activated carbons 20 . This is due to their large surface area, high adsorption capacity and some content of surface functional groups—often giving to the carbon surface properties enhancing adsorption.…”
Section: Introductionmentioning
confidence: 99%